1.已知x+4y=-1,xy=5,求(6xy+7y)+[8x-(5xy-y+6x)]的值.
(请写出步骤)
2.若a3+b3=35,a2b-ab2=-6,则(a3-b3)+(3ab2-a2b)-2(ab2-b3)的值是多少?
(请写出步骤)
3.
若2x+5y+4z=6,3x+y-7z=-4,那么x+y-z的值是多少?
(请写出步骤)
1.已知x+4y=-1,xy=5,求(6xy+7y)+[8x-(5xy-y+6x)]的值.
(请写出步骤)
2.若a3+b3=35,a2b-ab2=-6,则(a3-b3)+(3ab2-a2b)-2(ab2-b3)的值是多少?
(请写出步骤)
3.
若2x+5y+4z=6,3x+y-7z=-4,那么x+y-z的值是多少?
(请写出步骤)
1.
x+4y=-1,xy=5
(6xy+7y)+[8x-(5xy-y+6x)]=6xy+7y+8x-5xy+y-6x=xy+8y+2x=xy+2(x+4y)=5-2=3
2.a3+b3=35,a2b-ab2=-6
(a3-b3)+(3ab2-a2b)-2(ab2-b3)=a3-b3+3ab2-a2b-2ab2+2b3=(a3+b3)+(a2b-ab2)=35-6=29
3.2x+5y+4z=6
等式两边分乘3得6x+15y+12z=18
3x+y-7z=-4
等式两边分乘2得6x+2y-14z=-8
两式相减得13y+26z=26 即y+2z=2将此结果再分别代入以上两等式
2x+5y+4z=2x+3y+2(y+2z)=2x+3y+2x2=6 即2x+3y=2
3x+y-7z=3x+(y+2z)-9z=3x+2-9z=-4 即3x-9z=-6 所以x-3z=-2
上两式相加得2x+3y+x-3z=0 即3x+3y-3z=0 所以x+y-z=0
解:1、(6xy+7y)+[8x-(5xy-y+6x)]=(30+7y)+[8x-(25-y+6x)]=30+7y+8x-25+y-6x=5+8y+2x=3.
解:2、(a3-b3)+(3ab2-a2b)-2(ab2-b3)=a3-b3 +3ab2-a2b-2ab2+2b3=a3+b3 +3(ab2-a2b)=17.
解:3、